The Students' Perception of Using Vocabulary Tree in Learning English - Rustan, Rustan; Darwis, Nirwana; Resyadi, Herman (English Education Study Program, 2023)
This study aims to find out studentsâ€™ perception of using vocabulary tree in learning English. This research uses qualitative method with case study design. There are 18 students involved in this research which is chosen purposively. The data were collected through questionnaire, interview, and observation. The data were analyzed using Miles and Huberman model. The findings shows that students have perception positive responses, the enjoyment of the learning experience, and have vocabulary improvement. The majority of the students have perception of enjoy the vocabulary tree because it is a fun way of learning English. The data also shows that the students have enthusiasm in learning English using vocabulary tree and they also said can make simple sentences after learning using vocabulary tree. Some challenges are also detected but not much, some students are difficult to understand the meaning of words and making good sentences.Â